Emergency wireless broadband random access performance analysis with packet retransmission mechanism. (1st January 2012) - Gao, Zilong; Hu, Tianli; Huang, Lianfen; Lian, Lili; Lo, Chi-Hsiang
The random access channel model with retransmission packet mechanism is studied in the emergency wireless broadband access network (EWBAN). The success probability and access time delay packet request for MAC protocol access in EWBAN is analysed. The random access channel model with EWBAN retransmission packet mechanism and the MAC protocol is established using simulation results. Theoretical and engineering application guidance is provided for emergency wireless broadband communications.